Identification of ROS1 rearrangement in gastric adenocarcinoma. Issue 9 (7th February 2013) - Lee, Jeeyun; Lee, Seung Eun; Kang, So Young; Do, In‐Gu; Lee, Sujin; Ha, Sang Yun; Cho, Jeonghee; Kang, Won Ki; Jang, Jiryeon; Ou, Sai‐Hong Ignatius; Kim, Kyoung‐Mee
Abstract: BACKGROUND: Recently, chromosomal rearrangements involving receptor tyrosine kinases (RTKs) have been described in common epithelial malignancies, including nonsmall cell lung cancer (NSCLC), colorectal cancer, and breast cancer. One of these RTKs, c‐ros oncogene 1, receptor tyrosine kinase (ROS1), has been identified as a driver mutation in NSCLC, because its inhibition by crizotinib, an anaplastic lymphoma receptor tyrosine kinase (ALK)/met proto‐oncogene hepatocyte growth factor receptor (MET)/ROS1 inhibitor, led to significant tumor shrinkage in ROS1 ‐rearranged NSCLC. Currently, only human epidermal growth factor 2 (HER2)‐targeted therapy in combination with chemotherapy has been successful in significantly prolonging the survival of patients with advanced gastric cancer (GC). There is a need for the discovery of additional novel targets in GC. METHODS: Anti‐ROS1 immunohistochemistry (IHC) was used to screen 495 GC samples and was followed by simultaneous ROS1 break‐apart fluorescence in situ hybridization (FISH) and reverse transcriptase‐polymerase chain reaction (RT‐PCR) analyses in IHC‐positive samples. Fusion partners in ROS1 ‐rearranged GC were determined by RT‐PCR. In all 495 samples, HER2 amplification was identified with FISH, and MET expression was identified by IHC. RESULTS: Twenty‐three tumor samples were ROS1 IHC‐positive. Three of 23 patients were ROS1 FISH positive, HER2 FISH negative, and negative for MET overexpression; and 2 of those 3 patients harbored a solute carrier family 34 (sodium phosphate), member 2 ( SLC34A2) ‐ ROS1 fusion transcripts. No fusion partner was identified in the third patient. Both patients who had SLC34A2 ‐ ROS1 transcripts had poorly differentiated histology with recurrence and death within 2 years of curative surgery. ROS1 IHC‐positive status was not identified as an independent prognostic factor for overall survival. CONCLUSIONS: In this study, an SLC34A2 ‐ ROS1 rearrangement was identified in GC, and the results provide a rationale for investigating the clinical efficacy of ROS1 inhibitors in this unique molecular subset of GC. Cancer 2013. © 2013 American Cancer Society. Abstract : An SLC34A2 ‐ ROS1 rearrangement is identified in gastric carcinoma (GC) that is unique from human epidermal growth factor receptor HER2 ‐amplified GC. The results provide a rationale for investigating the clinical efficacy of ROS1 inhibitors in this unique molecular subset of GC.